Heterogeneous personal computing: a case study in materials science - Oliveira, Nuno (2017)
The HRTE Platform (Heterogeneous Run-Time Environment) Enables The Construction Of Problem Solving Environments Dedicated To A Specific Area (PSE) That Exploit The Heterogeneous Processing Resources Available In A Desktop Computer (Eg GPU). The HRTE-Enabled PSE Supports The Inter-Operation Between Existing Processing Modules And New Ones (Hmodules), Optimizing The Typical Communication Patterns Of A PSE. Hmodules Can Register Multiple Implementations Allowing HRTE To Select The Target Device At Runtime. The Main Features Of HRTE And The Programming Interface Used To Build Hmodules Are Described. An Application In The Materials Science Area Illustrates The Approach And Allows Us To Show Some Promising Performance Figures.